Diabetes Melitus Tipe 2 pada Pasien Neurodermatitis: Laporan Kasus - Syahrani Alya Murfi; Tutik Ernawati (Medula, 2026)
Neurodermatitis is a cutaneous manifestation that may exacerbate the clinical course of type 2 diabetes mellitus (T2DM); however, reports on the comprehensive management of these coexisting conditions in the primary healthcare setting remain limited. This case report aims to describe the successful implementation of an integrated management approach in a 55-year-old male patient with T2DM accompanied by neurodermatitis. The patient presented with paresthesia in both lower extremities, polyuria, polydipsia, and a chronic pruritic lesion with lichenification on the left upper arm. Random blood glucose measurement of 240 mg/dL supported the diagnosis of T2DM accompanied by neurodermatitis. Management included metformin therapy, appropriate topical treatment, intensive education on T2DM dietary management, lifestyle modification, increased physical activity, and family involvement to enhance treatment adherence. During follow-up evaluation, the patient's paresthesia, hyperglycemic symptoms, and cutaneous pruritus improved, fasting blood glucose decreased to 117 mg/dL, and the knowledge scores of both the patient and family increased from a pre-test score of 70 to a post-test score of 100. This case demonstrates that optimal glycemic control, accompanied by appropriate neurodermatitis management and family-based education, can lead to clinical improvement and enhance patient adherence to treatment. A comprehensive approach in the primary healthcare setting is essential for controlling cutaneous manifestations while preventing the progression of complications associated with T2DM.